How Does Liquid-Liquid Phase Separation in Model Membranes Reflect Cell Membrane Heterogeneity? - Sezgin, Erdinc; Sych, Taras (Karolinska Institutet, 2021)
It contains figures from Sych et al, Membranes, 2021.
First figure shows visualization of phase separation in synthetic and cell-derived membrane systems using phase selective probesSecond figure shows membrane order in liquid-ordered and liquid-disodered phases of synthetic and cell-derived membranes.Figures are provided in Inkscape svg format. Images are taken with confocal microscopy, and generalized polarization map was generated by using custom FiJi software (Sezgin et al, ChemPhysChem, 2015).

## Abstract of the paper
Although liquid–liquid phase separation of cytoplasmic or nuclear components in cells has
been a major focus in cell biology, it is only recently that the principle of phase separation has been
a long-standing concept and extensively studied in biomembranes. Membrane phase separation
has been reconstituted in simplified model systems, and its detailed physicochemical principles,
including essential phase diagrams, have been extensively explored. These model membrane systems
have proven very useful to study the heterogeneity in cellular membranes, however, concerns have
been raised about how reliably they can represent native membranes. In this review, we will discuss
how phase-separated membrane systems can mimic cellular membranes and where they fail to
reflect the native cell membrane heterogeneity. We also include a few humble suggestions on which
phase-separated systems should be used for certain applications, and which interpretations should
be avoided to prevent unreliable conclusions.
Researchers are welcome to use the data contained in the dataset for any projects. Please cite this metadata record upon use or when published. We encourage reuse using the same CC BY 4.0 License.

# Software to open files:
.csv - Microsoft Excel
.tif, .lsm - Fiji (https://imagej.net/Fiji.html#Downloads)
.pzfx - GraphPad Prism
.svg - Inkscape (https://inkscape.org/)
Keywords: Animal physiology - biophysics; Human biophysics; Medical and Health Sciences; Medicin och hälsovetenskap; Biophysics; Biofysik